A survey of neonicotinoid use and potential exposure to northern bobwhite (Colinus virginianus) and scaled quail (Callipepla squamata) in the Rolling Plains of Texas and Oklahoma. (14th April 2016) - Turaga, Uday; Peper, Steven T.; Dunham, Nicholas R.; Kumar, Naveen; Kistler, Whitney; Almas, Sadia; Presley, Steven M.; Kendall, Ronald J.
Abstract: Northern bobwhite (quail) ( Colinus virginianus ) and scaled quail ( Callipepla squamata ) populations have declined dramatically in the Rolling Plains ecoregion of Texas and Oklahoma (USA). There is rising concern about potential toxicity of neonicotinoids to birds. To investigate this concern, the authors examined crops of 81 northern bobwhite and 17 scaled quail to determine the presence or absence of seeds treated with 3 neonicotinoids (clothianidin, imidacloprid, and thiamethoxam). No treated seeds were found in the 98 crops examined. Liver samples from all 98 quail were collected and analyzed for neonicotinoid residues. Analysis revealed very low concentrations of neonicotinoids within the quail liver samples. The results suggest there is little to no risk of direct toxicity to quail from neonicotinoids. Environ Toxicol Chem 2016;35:1511–1515. © 2015 SETAC